2017
DOI: 10.1097/aog.0000000000002262
|View full text |Cite
|
Sign up to set email alerts
|

Inpatient Postpartum Long-Acting Reversible Contraception

Abstract: Inpatient insertion of long-acting reversible contraceptives (LARC) (intrauterine devices and implants) is increasingly offered to women immediately after childbirth. Enthusiasm for this approach stems from robust safety, effectiveness, and cost-effectiveness data, and responsiveness to women’s needs and preferences. While clinical evidence for immediate postpartum LARC is well-established, the ethical implications of enhancing access to this care have not been fully considered. Contraceptive policies and prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 17 publications
0
37
0
Order By: Relevance
“…Some women report feeling pressure from providers to choose a birth control method at the time of abortion [16,30]. Clinicians should respect patient autonomy, including the choice to not adopt a contraceptive or to choose a less-effective method, and take care to avoid contraceptive coercion [31][32][33].…”
Section: How Should Contraceptive Counseling Be Performed At the Timementioning
confidence: 99%
“…Some women report feeling pressure from providers to choose a birth control method at the time of abortion [16,30]. Clinicians should respect patient autonomy, including the choice to not adopt a contraceptive or to choose a less-effective method, and take care to avoid contraceptive coercion [31][32][33].…”
Section: How Should Contraceptive Counseling Be Performed At the Timementioning
confidence: 99%
“…Shared decision making can be a partnership in which the midwife has the ability to limit potential coercion and close gaps in comprehension or recall . Furthermore, Moniz et al suggest that immediate postpartum options should be presented even in the face of reimbursement or other challenges, including religious proscriptions, as a means to promote reproductive justice.…”
Section: Shared Decision Making and Mitigating Coercionmentioning
confidence: 99%
“…However, this option is underused because of barriers at the clinician, institution, and system levels . Barriers include knowledge gaps, challenges to implementing immediate postpartum IUD programs institutionally, reimbursement apart from the global fee, and racial and ethnic bias . Moniz et al found that, among midwives surveyed, clinician‐level barriers exist, including knowledge gaps around IUD expulsion rates, eligibility, and technique.…”
Section: Introductionmentioning
confidence: 99%
“…Enthusiasm for this approach stems from robust safety, efficacy, and cost‐effectiveness data, and responsiveness to patient needs and preferences. Although clinical evidence for immediate postpartum LARC is well established, the ethical implications of both the timing of when to offer contraceptive counseling and the enhanced access to this care have not been fully considered . For Black birthing people, this type of clinical practice could be considered a form of reproductive coercion.…”
Section: A Critical Race Lensmentioning
confidence: 99%
“…Although clinical evidence for immediate postpartum LARC is well established, the ethical implications of both the timing of when to offer contraceptive counseling and the enhanced access to this care have not been fully considered. 38 For Black birthing people, this type of clinical practice could be considered a form of reproductive coercion. A clinician who has not considered or is not prepared to articulate and discuss eugenics and the history of experimentation and reproductive exploitation that Black communities have experienced until as recently as the 1980s is unprepared to adequately care for Black birthing people.…”
Section: Relationship-centered Care Principle 3: All Health Care Rementioning
confidence: 99%